The Effect of Multilevel Rectifiers on Power Quality in Urban Electric Traction Systems - Rahmad, Supri (Journal of Electrical Engineering, 2024)
This study examines the effect of multilevel rectifiers on power quality in urban electric traction systems. Electric traction systems used for public transportation, such as trains and trams, require high power quality to ensure efficient operation and reduce interference on the power grid. One key component in these systems is the rectifier, which converts alternating current (AC) to direct current (DC) for traction motors. Multilevel rectifiers offer several advantages over conventional rectifiers, including harmonic reduction, increased efficiency, and reduced voltage distortion that can affect motor performance and overall power quality. This study explores how the use of multilevel rectifiers can reduce current and voltage harmonics in electric traction systems, as well as their impact on power factor and operational efficiency. Using simulations and experimental analysis across various traction system operating scenarios, the results show that multilevel rectifiers can significantly improve power quality, reduce harmonic distortion, and increase the system power factor. Furthermore, the implementation of multilevel rectifiers has been shown to reduce heat generation by power electronic components, which in turn increases equipment reliability and operational life. Thus, this study demonstrates that the use of multilevel rectifiers in urban electric traction systems not only improves power quality but also offers a solution to increase energy efficiency and reduce the environmental impact of electric transportation systems. The implementation of this technology could be a crucial step in the development of intelligent and sustainable transportation systems.